Computational fluid dynamics simulation from microCT stacks of commercial biomaterials usable for bone grafting. (June 2020) - Chappard, Daniel; Kün-Darbois, Jean-Daniel; Guillaume, Bernard
Graphical abstract: Highlights: Granules of biomaterials form 3D porous arrangements whose geometry depends on the size and shape of the granules. Microcomputed tomography is a suitable tool to analyze their 3D microarchitecture. The images can be used to simulate body fluid flow through the stacks of granules. Stacks of large granules present a suitable fluid drainage, small granules or putties have very reduced fluid flow. Simulation of fluid flow is an interesting tool to mimic the invasion of body fluid and bone progenitor cells in vivo . Abstract: Granules of calcium/phosphate biomaterials are used to fill small bone defects in oral and maxilla-facial surgery. Granules of natural (e.g., trabecular bone, coral) or synthetic biomaterials are provided by industry. Small granules can also form of putty. The 3D geometry of granules creates a macroporosity allowing invasion of vascular and bone cells when pores are larger than 300 μm. We analyzed the 3D-porosity of 11 different stacks of biomaterials: Osteopure®, CopiOs®, Bio-Oss®, TCP Dental HP®, KeraOs®, TCH®, Biocoral®, EthOss® and Nanostim®. For each granular biomaterial, two sizes of granules were analyzed: small and large. Microcomputed tomography (microCT) determined porosity and microarchitectural characteristics of the biomaterials stacks. Computational ﬂuid dynamics (CFD), a simulation method, was used on the stacks of microCT images. Stacks of small granules had a much lower permeation and fluid velocity than large granules and the hydraulic tortuosity was increased. Significant correlations were observed between microarchitecture parameters (porosity, mean pore diameter and specific surface) and fluid dynamic parameters. The two putties were associated with low (or absence of) porosity and permeation study revealed a very low (or absence) of flow rate. Stacks of granules represent 3D scaffolds resembling trabecular bone with an interconnected porous microarchitecture. Small granules create pores less than 300 μm in diameter; this induces a low fluid flow rate. CFD simulates the accessibility of body fluids and progenitor cells and confirms that it is depending on the shape and 3D arrangements of granules within a stack. Large granules must be preferred to putties and small granules.